Effect of Growth Rate Population and Poverty To Economic Growth in North Sumatra for the 2012-2023 Period - Sianturi, Tasya G; Vidia Wardana; Selfiana Lumban Batu; Eva J Situmorang; Chia-Yu (Outline Publisher, 2024)
This research aims to analyze the influence of population growth rates and poverty on economic growth in North Sumatra Province for the 2012-2023 period. The research method used is a quantitative method. The regression analysis method is multiple linear regression using the Eviews 12 program and the data used is a time series from 2012-2023 sourced from the North Sumatra Central Bureau of Statistics (BPS SUMUT). The results of the analysis show that the variable values of population growth rate and poverty have a positive but not significant effect on economic growth in North Sumatra.